2020
DOI: 10.3389/fpsyg.2020.00295
|View full text |Cite
|
Sign up to set email alerts
|

I’m Not Good for Anything and That’s Why I’m Stressed: Analysis of the Effect of Self-Efficacy and Emotional Intelligence on Student Stress Using SEM and QCA

Abstract: Stress negatively affects the well-being and the quality of life of the society. Specifically in the academic context, it is relevant to analyze its levels due to its impact on performance and learning. There are factors that affect the said stress including, among others, self-efficacy, and emotional intelligence. The purpose of this study is to analyze how emotional intelligence and perceived self-efficacy affect student stress. In order to show this influence, two complementary methodologies are implemented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
27
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 77 publications
(142 reference statements)
6
27
0
6
Order By: Relevance
“…Regarding the first hypothesis, the data showed that there was an inversely proportional relationship between the perception of academic self-efficacy and anxiety, both TA and SA, results in line with the research of Gutiérrez-García and Landeros-Velázquez (2018) , Navarro-Mateu et al (2020) , and Colom (2012) . One explanation might be that anxiety is related to both cognitive and motivational and emotional processes.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Regarding the first hypothesis, the data showed that there was an inversely proportional relationship between the perception of academic self-efficacy and anxiety, both TA and SA, results in line with the research of Gutiérrez-García and Landeros-Velázquez (2018) , Navarro-Mateu et al (2020) , and Colom (2012) . One explanation might be that anxiety is related to both cognitive and motivational and emotional processes.…”
Section: Discussionsupporting
confidence: 86%
“…These motivational characteristics could negatively affect the expectations of self-efficacy that, together with the demands of the university context, could interfere with their academic aspirations ( Ahmadi, 2020 ). In addition, the psychological pressure of the confinement ( Xiao, 2020 ) was joined to the academic demands, workload, and online evaluations that could negatively affect the perception of academic self-efficacy ( Navarro-Mateu et al, 2020 ), generating higher levels of anxiety in university students ( Huarcaya-Victoria, 2020 ). In addition, not attending classes due to the closure of universities was a factor of concern and anxiety ( Kelly, 2020 ), since the work methodology changed ( Abreu, 2020 ) when the students were not prepared.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When performing the fuzzy-set qualitative comparative analysis, the raw data from the participants' responses were transformed into fuzzy-set responses. First, all the missing data were deleted as suggested in the literature, and all constructs (variables) were calculated by multiplying their item scores (Villanueva et al, 2017;Giménez-Espert and Prado-Gascó, 2018;Navarro-Mateu et al, 2020). Before performing the analysis, the values were recalibrated between 0 and 1.…”
Section: Discussionmentioning
confidence: 99%